Delicate condition ebook - Valentine, Danielle (2023)
THE INSPIRATION FOR FX'S AMERICAN HORROR STORY: DELICATE STARRING EMMA ROBERTS AND KIM KARDASHIAN A GOOD MORNING AMERICA BUZZ PICK As seen in People, Vanity Fair, Variety, Entertainment Weekly, USA Today, Shondaland, and more! Anna Alcott is desperate to have a family. But as she tries to balance her increasingly public life as an indie actress with a grueling IVF journey, she starts to suspect that someone is going to great lengths to make sure that never happens. Crucial medicines are lost. Appointments get swapped without her knowledge. Cryptic warnings have her jumping at shadows. And despite everything she's gone through to make this pregnancy a reality, not even her husband is willing to believe that someone is playing twisted games with her. Then her doctor tells her she's had a miscarriage—except Anna's convinced she's still pregnant despite everything the grave-faced men around her claim. She can feel the baby moving inside her, can see the strain it's taking on her weakening body. Vague warnings become direct threats as someone stalks her through the bleak ghost town of the snowy Hamptons. As her symptoms and sense of danger grow ever more horrifying, Anna can't help but wonder what exactly she's carrying inside of her...and why no one will listen when she says something is horribly, painfully wrong.